Analysis of IFAS, EFAS Strategies and Feasibility of Mangot Cultivation Business to Reduce Household Waste : ANALYSIS OF IFAS, EFAS STRATEGY AND FEASIBILITY OF MANGGOT CULTIVATION BUSINESS TO REDUCE HOUSEHOLD WASTE - Ratniati, Ni Ketut; Elik Astari, Anak Agung; Andini Desiyanti Laksmi, Ni Putu (Program Studi Akuntansi Universitas Islam Lamongan, 2023)
This study aims to analyze the strategy and feasibility of the Maggot cultivation business of the Renon Trash Maggot (RTM) Joint Business Group (KUBE) located in Renon Village, Denpasar City, this business helps decompose household waste, in its role of caring for sustainable development, using EFAS, EFAS, Matrix SWOT, QPSM analysis methods where the results of the analysis found that the business of KUBE RTM is in the Growth and Build zone, and strategies suitable for this zone are intensive (market penetration, product development) or integration (backward integration, front integration, and horizontal integration) and from the business feasibility of the financial aspect of net present value (NPV) analysis the results are positive, the internal rate of return (IRR) results are 30%, the profitability index (PI) results are > 1 which is 1.2 times and the business payback period (PP) is 10 months, 28 days.